If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -7y + 4 = 2y + 11 + -7y Reorder the terms: 3 + 4 + -7y = 2y + 11 + -7y Combine like terms: 3 + 4 = 7 7 + -7y = 2y + 11 + -7y Reorder the terms: 7 + -7y = 11 + 2y + -7y Combine like terms: 2y + -7y = -5y 7 + -7y = 11 + -5y Solving 7 + -7y = 11 + -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. 7 + -7y + 5y = 11 + -5y + 5y Combine like terms: -7y + 5y = -2y 7 + -2y = 11 + -5y + 5y Combine like terms: -5y + 5y = 0 7 + -2y = 11 + 0 7 + -2y = 11 Add '-7' to each side of the equation. 7 + -7 + -2y = 11 + -7 Combine like terms: 7 + -7 = 0 0 + -2y = 11 + -7 -2y = 11 + -7 Combine like terms: 11 + -7 = 4 -2y = 4 Divide each side by '-2'. y = -2 Simplifying y = -2
| 120(20)=50(x) | | (2(3)-a)(3+b)(3+c)=0 | | x-(3-x+1)=-x-4 | | x-3(-x+1)=-x-4 | | f(x)=1+ln(1+ln(1+ln(1+x))) | | 19-(5m+7)=4+2m-13 | | 60(36)=60(k) | | (2b-1)i+(a+3)=4-8i | | 4t^2-20t-25=0 | | (3x-5)+(12x)=90 | | (3-2i)-(2x+yi)=7+6i | | 3a-10+4a=5a-7 | | 3.7b+7=8.1b-18.4 | | 42(z)=35(28) | | 4+3+-7=4+-7 | | 36(x)=45(32) | | (2x)=(2y-x) | | (3x-5)=(12x) | | C(x)=.6x+30 | | x-3(-x)+1=-x-6 | | 18(5)=7.5(x) | | 10-(3x-5)=11-4x | | 8+3x=132 | | 10x-50=7x-20 | | x-(3-x+1)=-x-6 | | X^2-11x+48=0 | | 11x-8=x | | 0=(-.02x^2)+1.7x+5.1 | | 90+2x-3+4x+11=180 | | 180=(180-(8x+10))+2x+10+x+30 | | X+6c=180 | | -2(-6-1)+3(-6+4)=8 |